Peningkatan Produktivitas Kerja Melalui Penguatan Motivasi Karyawan Pada Bumdes Kamuning Jaya Desa Cikamunding - Riki Haryono; Ahmad Ghoni (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
The Community Service activity was entitled "Increasing Work Productivity through Strengthening Employee Motivation at BUMDes Kamuning Jaya Cikaunding Village." The main problem faced by BUMDes Kamuning Jaya is the lack of optimal employee work productivity caused by low work motivation, lack of understanding of the importance of target-based performance, and the absence of a structured human resource management system. This condition has an impact on the achievement of organizational goals and the contribution of BUMDes to the improvement of the village economy. The solution offered in this activity is the implementation of education and training programs that focus on strengthening employee work motivation as the main factor in increasing productivity. This activity will provide an understanding of the concept of work motivation, factors that affect motivation, and strategies to increase work morale and commitment. In addition, participants will also be equipped with an understanding of the importance of work productivity, performance indicators, and how to increase work effectiveness and efficiency in organizations.The activity plan includes several stages, namely: (1) preparation and coordination stage with BUMDes and village governments; (2) identification of problems and needs of partners; (3) the implementation of education and training through lectures, discussions, and case study methods; (4) assistance in the application of work motivation and productivity improvement; and (5) monitoring and evaluation through pre-test and post-test to measure the improvement of understanding and changes in employee work behavior. The purpose of this PKM activity is to provide socialization to members/employees of Bumdes Kamuning Jaya related to productivity and strengthening work motivation. The results of the evaluation show a significant increase in all aspects of knowledge with an average increase of 39 percentage points from pre-test to post-test. This proves that this PKM activity is effective in improving the village, work morale, self-development, achievements, awards and responsibilities.